Therapeutic robots as a technological intervention in residential environments for older adults: Uses, limitations and ethical concerns - Redolat, Rosa; Fernández-Rios, Mercedes (Technium Social Sciences Journal, 2021)
The use of Information and Communication Technologies (ICTs) is one of the innovative responses to the high prevalence of Alzheimer’s Disease (AD) and other neurodegenerative disorders. A more holistic approach to the field of gerontology is being adopted, including robotics as an expanding field in the care of the elderly. Our main aim is to review how new technologies can provide opportunities for sensory stimulation and social participation for older adults. We also discuss the transformation of the models of care (from more traditional medical models to person-centered care models) reviewing the use of social robots as a valuable tool in interventions in different residential environments. Robotic technology aimed at the support and care for older adults has shown benefits in areas such as communication, social interaction and quality of life. The review of recent literature also suggests that the use of social robots presents some limitations (robots should be designed to meet the real needs of patients and we need to take into account their impact on health and environment) and ethical concerns (data protection or fear that robots will end up replacing contact among humans) that must be considered when applying these new technologies. It is concluded that social robots can be considered as promising tools for use in people with AD, both from the perspective of the patients and their caregivers, offering cost-effective solutions. New technologies should not aim to replace humans but rather could be a complementary tool for the management and provision of care.